Emerging challenges for Risk Management in Chemical, Biological and Radiological Research and Development - David Heslop (Global Biosecurity, 2019)
The challenges associated with effective risk management, and the risks of proliferation and developing offensive and defensive capability when working with Chemical, Biological and Radiological agents have recently been highlighted on the world stage. Work in any of the three primary dimensions of CBRNE research and production carries a myriad of potential and actual risks that require careful control, and to avoid individual through to population impacts. Failures in risk controls can result not only in personal injury but also expose the wider population to significant and persistent risks. This editorial touches on some of the recent events relating to work with CBRNE agents, and highlights the challenges faced by the current increasing tempo of research and development in this area.